THE DIAGNOSTIC VALUE OF MRI IN PRE-OPERATIVE ASSESSMENT OF PERIANAL FISTULA IN ISLAMABAD-PAKISTAN: A RETROSPECTIVE, OBSERVATIONAL STUDY (The Research of Medical Science Review, 2025)
inner lining to the surrounding skin, often causing significant discomfort and reducing quality of life. Picture a straight, inflamed, and scarred passage from the skin to the lower anus. In cases involving prior surgery or Crohn's disease, the fistula may become complex, branching deeper into the body.Objective: To investigate the accuracy of MRI (magnetic resonance imaging) in the pre-op valuation of perianal fistulas recognizing the importance of precise anatomical mapping for successful surgical management in this regional setting.Methodology: A retrospective observational study was conducted on 140 patients diagnosed with perianal fistula between August 2024 and December 2024. Patient demographics, clinical presentation, and MRI findings were analyzed. Fistula classification was based on the St. James University Hospital system.Results: The mean age of the participants was 40 years. Inter-sphincteric fistulas were the most common (64.28%), followed by trans-sphincteric (31.42%). We frequently observed intricate fistulas, often accompanied by additional pathways, pus-filled pockets, and horseshoe-shaped extensions. MRI accurately recognized internal openings, tract lengths, and spatial relationships to anal sphincters. The most common location for the internal opening was the 6 o'clock position.Conclusion: Pre-op MRI stands out as an indispensable tool for the precise diagnosis of perianal fistula anatomy. By offering detailed insights into the complexity and spatial relationships of the fistula, MRI significantly enhances surgical planning. This detailed information is crucial, as it has the potential to reduce postoperative recurrence rates, ultimately leading to better outcomes for patients.